2022
DOI: 10.3390/microorganisms10030654
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Commensal Bifidobacteria Strains in Gut Microbiota of Neonates Born Preterm: A Prospective Longitudinal Study

Abstract: Bifidobacterial population dynamics were investigated using a longitudinal analysis of dominant species isolated from feces of neonates born preterm (singletons (n = 10), pairs of twins (n = 11)) from birth up to 16 months of age. We performed quantification, isolation, and identification of the dominant bifidobacteria strains. The genetic relationship of the isolates was investigated via pulsed field gel electrophoresis (PFGE) genotyping, and PCR was used to screen the specific genetic marker tet genes. Addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 58 publications
(76 reference statements)
0
3
0
Order By: Relevance
“… 56 The child’s gut seems to be unstable and thus modifiable early in life as no differences were observed in the gut microbiota during the first week of life between vaginally delivered children and children born via caesarean section but after 2 weeks certain differences were noticeable. 57 Likewise, a previous study 58 assessed the longitudinal changes of the populations of bifidobacteria in preterm children’s guts during their first year of life and concluded that there are fluctuations in the species, strains, and the gene expression of bifidobacteria, indicating that early external factors, or probiotic interventions, are able to modify the preterm microbiota. Indeed, it is not too late to begin the modification of the preterm child’s microbiota after birth.…”
Section: Discussionmentioning
confidence: 99%
“… 56 The child’s gut seems to be unstable and thus modifiable early in life as no differences were observed in the gut microbiota during the first week of life between vaginally delivered children and children born via caesarean section but after 2 weeks certain differences were noticeable. 57 Likewise, a previous study 58 assessed the longitudinal changes of the populations of bifidobacteria in preterm children’s guts during their first year of life and concluded that there are fluctuations in the species, strains, and the gene expression of bifidobacteria, indicating that early external factors, or probiotic interventions, are able to modify the preterm microbiota. Indeed, it is not too late to begin the modification of the preterm child’s microbiota after birth.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, the single-centre PREMAFLORA cohort (ANR-07-PNRA-007) enrolled infants of gestational age less than 37 weeks hospitalized in a French NICU (2008–09). 19 Both the EPIFLORE (2011) and ClosNEC (2015–16) cohorts were multicentre NEC case–control studies involving 12 French NICUs, enrolling preterm neonates with gestational age less than 32 weeks . 9 , 20 No NEC outbreak was reported during the inclusion periods.…”
Section: Methodsmentioning
confidence: 99%
“…1 ). The PREMAFLORA cohort (ANR-07-PNRA-007) included infants less than 37 weeks of gestational age who were hospitalized at a French NICU between 2008 and 2009 ( 20 ). The EPIFLORE study took place in 2011, and the ClosNEC study was conducted between 2015 and 2016.…”
Section: Methodsmentioning
confidence: 99%